Fire management in the Brazilian savanna: First steps and the way forward. Issue 5 (4th March 2018) - Schmidt, Isabel B.; Moura, Lívia C.; Ferreira, Maxmiller C.; Eloy, Ludivine; Sampaio, Alexandre B.; Dias, Paulo A.; Berlinck, Christian N.
Abstract: Several decades of frustrated attempts to prevent fires in the Brazilian Savanna (Cerrado) have led to deleterious ecological and management consequences. In 2014, the first Integrated Fire Management (IFM) programme was launched in three protected areas (PAs). The IFM programme considers local practices, ecological information, management options and aims to create landscape mosaics of different fire histories to conserve biodiversity, reduce the prevalence of late‐dry season (LDS) wildfires, protect fire‐sensitive vegetation and reduce conflicts between PA managers and local communities. The first 3 years of imposed fire management regimes led to 40%–57% reduction in LDS fires, improved dialogue between researchers, managers and local communities, generating fire management learning communities. Synthesis and applications . This Integrated Fire Management programme represents a major advance in Cerrado management and conservation, by actively managing fires and decreasing the proportion of areas burnt by late‐dry season wildfires. It can contribute to PAs' management in the Cerrado and other South American fire‐prone ecosystems. Long‐term monitoring and research are essential to understand the ecological implications and to improve fire management practices. Abstract : This Integrated Fire Management programme represents a major advance in Cerrado management and conservation, by actively managing fires and decreasing the proportion of areas burnt by late‐dry season wildfires. It can contribute to PAs' management in the Cerrado and other South American fire‐prone ecosystems. Long‐term monitoring and research are essential to understand the ecological implications and to improve fire management practices.